Stress detection and relief using wearable physiological sensors - Kriti Sethi; T. Ramya; Hanut Pratap Singh; Rishik Dutta (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The aim of the paper was to present a concept and to develop a prototype in the form of a cap which uses a combination of physiological sensors that work in concert to not only detect high stress levels in a person during his daily routine and working env ironment, but also initiate immediate relief measures. The parameters used to detect stress were compared with resting heart rate and brainwave activity to determine whether the person wearing the cap is in a stressed condition. Stress alleviation was achieved using Auditory Stimulation and a Scalp Massage. Early detection of stress and its immediate remedy or reduction can play an important role in preventing mental health disorders. In order to make the product cost effective, the concept of sensing optimum amount of data to trigger a remedial action was given more importance than extensive data collection using large number of sensors. Integrating an IOT device will further allow information to be recorded and transmitted to a caregiver/doctor to prescribe remedial action and thus prevent the condition to take a pathological form or get complicated. The detailed analysis of the collected data can help people identify the precipitating factors for stress and thus aims at reduction of stress related illnesses.